2015
DOI: 10.1021/acs.langmuir.5b01165
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Electron Transfer of PAMAM Dendrimer–Zinc(II) Porphyrin Associates at Polarized Liquid|Liquid Interfaces

Abstract: The heterogeneous photoinduced electron-transfer reaction of the ion associates between NH2-terminated polyamidoamine (PAMAM) dendrimers and 5,10,15,20-tetrakis(4-sulfonatophenyl)porphyrinato zinc(II) (ZnTPPS(4-)) was studied at the polarized water|1,2-dichloroethane (DCE) interface. The positive photocurrent arising from the photoreduction of ZnTPPS(4-) by a lipophilic quencher, decamethylferrocene, in the interfacial region was significantly enhanced by the ion association with the PAMAM dendrimers. The phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…In metal ion extraction, a hydrophobic ligand is typically dissolved in the organic phase and coordinates with the metal ion either interfacially or in the bulk organic/aqeuous phase [13,14]. Conventional means of separation have been through physical mixing of the two phases [9,15]; however, as previously demonstrated [10][11][12]16], this process can also be investigated electrochemically using liquid|liquid electrochemistry performed at a polarizable interface between two immiscible electrolytic solutions (ITIES) [13,14,[17][18][19][20][21]. Furthermore, in order to reduce samples sizes and improve sensitivity, a micro-ITIES is often employed, such as at the tip of a pulled borosilicate glass capillary [11,16,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In metal ion extraction, a hydrophobic ligand is typically dissolved in the organic phase and coordinates with the metal ion either interfacially or in the bulk organic/aqeuous phase [13,14]. Conventional means of separation have been through physical mixing of the two phases [9,15]; however, as previously demonstrated [10][11][12]16], this process can also be investigated electrochemically using liquid|liquid electrochemistry performed at a polarizable interface between two immiscible electrolytic solutions (ITIES) [13,14,[17][18][19][20][21]. Furthermore, in order to reduce samples sizes and improve sensitivity, a micro-ITIES is often employed, such as at the tip of a pulled borosilicate glass capillary [11,16,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Photoinduced electron transfer reaction was also observed for similar porphyrin dimer and hexanethiolate monolayer protected gold nanoclusters dissolved in the DCE phase [76]. ZnTPPS 4+ association with positively charged polyallylamine polyelectrolyte and polyamidoamine dendrimers can also contribute to photocurrent amplification [77]. The best performance found for dendrimer-porphyrin conjugate was attributed to electrochemically driven interfacial deposit formation with high porphyrin loading and stable associate formation [41].…”
Section: Molecular Assembliesmentioning
confidence: 78%
“…30 Due to their similarities to natural dyes functioning in photosynthetic systems, supramolecular assemblies of zinc(II) 5,10,15,20-(tetra-4-carboxyphenyl)porphyrin (ZnTPPc) molecules at immiscible liquid|liquid interfaces are of particular interest for solar energy conversion and storage applications. 31,32 Early work demonstrated that photocurrents obtained at porphyrin nanostructure functionalised liquid|liquid interfaces are remarkably dependent on the light polarization, indicating a well-ordered self-assembled nanostructure due to the templating interaction of the interface. 33 Recently, our group demonstrated that these interfacial ZnTPPc nanostructures are stabilized by cooperative hydrogen bonding and likely represent metastable or kinetically trapped non-equilibrium nanostructures.…”
Section: Introductionmentioning
confidence: 99%